Application of Infrared Spectroscopy to Analysis of Chitosan/Clay Nanocomposites - Silva, Suédina M.L.; Braga, Carla R.C.; Fook, Marcus V.L.; Raposo, Claudia M.O.; Carvalho, Laura H.; Canedo, Eduardo L. (IntechOpen, 2012)
None